Occupational skin diseases among bricklayers and brick masons in a resource poor setting, Southwest Nigeria: prevalence and correlates – a case–control study - Michael Gbenga Israel; Oluwaseyi Kikelomo Israel; Adeolu Oladayo Akinboro; Peter Kehinde Uduagbamen; Sebastien S Oiwoh; Olanrewaju Olayemi; Fatai O Olanrewaju; Mufutau M Oripelaye; Stephen Olawale Aiyedun; Olumayowa Oninla; Olayinka Olasode; Olaniyi Onayemi (BMJ Open)
Objectives Cement and most other materials used by bricklayers and brick masons for construction purposes could heighten the risk for occupational skin diseases (OSDs) which mostly include occupational contact dermatitis (OCD) and others. The activities of the bricklayers or brick masons are essentially manual as they work as artisans involving mixing sands and gravels with cement and water for building and block moulding, respectively. This can lead to a significant decline in the quality of life and psychosocial function. We determined the prevalence of OSDs and their correlates among bricklayers and brick masons.Design This was a comparative case–control study which involved 200 bricklayers/brick masons and 200 healthy non-bricklayers/non-brick masons.Settings This study was carried out in two local governments (LGAs) in Ogbomoso community.Methods Respondents were selected using a multistage random sampling technique. Interviewer–administer semi-structured questionnaire was used to collect data. Data were analysed using descriptive statistics, the prevalence of OCD and other OSD were determined, χ2 test and logistic regression were obtained. A p<0.05 was considered as statistically significant.Results The mean age of the bricklayers/brick masons was 39.74±17.03 years, while that of the control group was 40.04±17.24 years. The prevalence of OCD was significantly higher in the bricklayers/brick masons (43.0%) than controls (5.5%), p<0.001. Other dermatological conditions were more common among the cases (8.5%) than the controls (5.0%), p=0.04. Bricklayers/brick masons not using personal protective equipment (PPE, hand gloves) were three times more likely to develop OCD compared with those who used them (OR=3.38, 95% CI 0.12 to 0.72, p=0.007). A family history of allergy is also a predictor of OCD (OR=2.69, 95% CI 1.30 to 5.60, p=0.008).Conclusion OSD are common in bricklayers/brick masons, especially among those without the use of PPE. Regular educational programmes emphasizing the need to reduce direct contact with cement including the proper and regular use of PPE among this population group are advised.